ANALYSIS OF SEDIMENTATION TRENDS IN EFFORTS FOR SUSTAINABILITY AT WONOREJO RESERVOIR - Novi Andriany Teguh; Nastasia Festy Marginia (FKIP USK, 2021)
Sedimentation is a natural problem that always occurs in water structures, especially dams and reservoirs. Wonorejo Reservoir as a multipurpose reservoir also experienced this. Sedimentation can affect the performance of reservoirs and dams. With the accumulation of sediment, the volume of the reservoir will change from time to time, so it is necessary to estimate the volume of sediment during the useful life of the reservoir and dam, so that they can function optimally. In addition, efforts are also needed to deal with the sedimentation. This study was conducted to estimate the volume of sediment that can occur during the useful life of reservoirs and dams, which is 50 years. Using limited data from previous studies, the study was carried out using the literature study method from other studies that have been carried out in other reservoirs and dams in Indonesia. Based on the estimation results, it is estimated that the volume of sediment in the Wonorejo Reservoir at the end of its age will reach 17.6% of the reservoir capacity volume. So it can be concluded that the reservoir can still work optimally. However, these results are not accurate enough due to the limited data available so that proper sedimentation management efforts are still needed. These countermeasures can be adopted from what has been suggested in other studies for reservoirs and dams in Indonesia.